Project Management Reference Framework (RF) for the Malaysian public projects / Mohd Firdaus Mustaffa Kamal - Mustaffa Kamal, Mohd Firdaus (Institute of Graduate Studies, UiTM, 2016)
The inconsistent performance of the public project delivery has spawned the needs to research and identify the underlying issues that affect the public project management capability. One essential finding contributing to this issue was the absence of a commonly recognized Reference Framework (RF) for the public project management. It has been conceived that the absence of such RF has resulted in the inadequate provision of the public project management standard of procedure (SOP) that has in part contributed to the poor performance of the public projects as been highlighted in series of the Auditors’ General Annual Report for the year 2012, 2013, 2014 and 2015. This research aims to propose a commonly recognized project management RF that can be used to assist in designing and identifying the provisional needs for the public project SOP…